Numerical and experimental modelling of dam break interaction with a sediment bed - McMullin, Nicholas (2015)
A dam break event is considered, taking place over a uniform sediment bed. Understanding and modelling the erosion that occurs when the fluid behind the dam collapses at release has important applications in coastline morphodynamics / beach erosion modelling.